Firm Attributes and Audit Report Timeliness: Evidence from Indonesia’s Property and Real Estate Sector - Retnowati, Wulan; Satibi, Satibi (Journal of Applied Business, Taxation and Economics Research, 2025)
Audit Report Lag (ARL) refers to the interval between the end of a financial reporting period and the release of audited financial statements. Timeliness in audit reporting plays a crucial role in improving the relevance of financial information, strengthening transparency, and fostering stakeholder trust. This study investigates the extent to which firm size, profitability, leverage, audit committee meeting frequency, and accounting complexity contribute to variations in ARL. A quantitative research design was employed using secondary data extracted from annual reports of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Using purposive sampling, 75 firm-year observations were analyzed. Multiple regression performed in SPSS 25 indicates that profitability and the frequency of audit committee meetings are associated with shorter ARL. Meanwhile, firm size, leverage, and accounting complexity do not exhibit significant relationships with ARL. These results contribute to agency theory and corporate governance scholarship by emphasizing governance-related mechanisms that facilitate more efficient audit completion